Proximity Ligation Assay (PLA) - Alam, Muhammad S (Curr Protoc Immunol, 2018)
Proximity ligation assay (PLA), also referred to as Duolink® PLA technology, permits detection of protein-protein interactions in situ (at distances < 40 nm) at endogenous protein levels. It exploits specific antibodies identifying (either directly or indirectly) the two proteins of interest and takes advantage of specific DNA primers covalently linked to the antibodies. A hybridization step followed by a PCR amplification with fluorescent probes then permit visualization of spots of proximity by fluorescence microscopy. Since the development of PLA in 2002, it has been increasingly popular to detect the interaction between two proteins with high sensitivity and specificity. It is a very simple and sensitive technique to study protein-protein interaction in cells.